EGFR-Dependent Extracellular Matrix Protein Interactions Might Light a Candle in Cell Behavior of Non-Small Cell Lung Cancer - Hassanein, Sarah Sayed; Abdel-Mawgood, Ahmed Lotfy; Ibrahim, Sherif Abdelaziz (Frontiers in Oncology, 2021)
Lung cancer remains the leading cause of cancer-related death and is associated with a poor prognosis. Lung cancer is divided into 2 main types: non-small cell lung cancer (NSCLC); the major in incidence, while the minor is small cell lung cancer (SCLC). Although NSCLC progression depends on driver mutations, it is also affected by the extracellular matrix (ECM) interactions that activate their corresponding signaling molecules in concert with integrins and matrix metalloproteinases (MMPs). These signaling molecules include cytoplasmic kinases, small GTPases, adapter proteins, and receptor tyrosine kinases (RTKs), particularly the epidermal growth factor receptor (EGFR). In NSCLC, the interplay between ECM and EGFR regulates ECM stiffness, angiogenesis, survival, adhesion, migration, and metastasis. Furthermore, some tumor-promoting ECM components (e.g., glycoproteins and proteoglycans) enhance activation of EGFR and loss of PTEN. On the other hand, other tumor-suppressing glycoproteins and -proteoglycans can inhibit EGFR activation, suppressing cell invasion and migration. Therefore, deciphering the molecular mechanisms underlying EGFR and ECM interactions might provide a better understanding of disease pathobiology and aid in developing therapeutic strategies. This review critically discusses the cross-talk between EGFR and ECM affecting cell behavior of NSCLC, as well as the involvement of ECM components in developing resistance to EGFR inhibition.